Epidermal Bioelectronics for Management of Chronic Diseases: Materials, Devices and Systems - Zheng Qiao; Shuwen Chen; Shicheng Fan; Ze Xiong; Chwee Teck Lim (Advanced Sensor Research, 2023)
Abstract Chronic diseases are currently posing a major challenge not only to our life expectancy and healthspan but also to the healthcare system, as patients will need continual monitoring, treatment, and care to mitigate some of the severe health complications that may arise. Merely frequent visits to medical facilities and clinics may not be sufficient. Home‐based point‐of‐care diagnosis and monitoring may be needed for the prevention and/or management of long‐term complications. Recent advances in materials, fabrication methods, and bioelectronics have led to some epidermal systems that can measure critical physiological parameters and provide long‐term monitoring of several chronic diseases. In this review, it is systematically outlined the progress of epidermal bioelectronics aimed at managing common chronic diseases, such as cardiovascular diseases, diabetes, and chronic wounds. Flexible and stretchable materials with related engineering approaches that render wearability are also discussed. Finally, a list of current challenges, future perspectives as well as potential research directions with the aim towards better translation in bringing these wearable technologies from the laboratory to the clinic and market are presented.